ESTUDO FÍSICO-QUÍMICO E DE TOXICIDADE DE NANOPARTÍCULA DE NARINGINA REVESTIDA COM QUITOSANA - Levy, Bruno Silveira (2023)
The central nervous system is the command center of the human body and the brain is an organ highly susceptible to oxidative stress. Therefore, neurological disorders pose significant health risks. Naringin is a flavonoid with antioxidant properties and potential health benefits, and nanoescapsulation can increase its neuroprotective activity, especially when combined with a direct delivery system to the brain via the intranasal route. Thus, the objective of this study is to produce a naringin nanoparticle coated with the mucoadhesive polymer chitosan through the nanoprecipitation method. For this, the physical-chemical parameters, 60-day stability at different storage temperatures (4, 25 and 40°C) and in vitro (HFF-1 fibroblast lineage) and in vivo (C. elegans) toxicity were evaluated. The observed results were average particle size of 175 ± 5.1 nm, polydispersity index of 0.152 ± 0.003, zeta potential of +13.1 ± 4.3 mV, content of 81.52 ± 0.78% and pH of 4.8 ± 0.16. The most suitable storage temperature for the suspensions was 25°C. In the in vitro toxicity assay by the MTT method, a decrease in cell proliferation and an increase in the production of reactive oxygen species were observed in the highest concentrations of nanoparticles, while in the in vivo assay, a high mortality and motor deficits in nematodes treated with the highest concentrations of nanoparticles were observed. In the total antioxidant capacity test, the nanoparticles were not able to show effects, while in the ferric reducing antioxidant power, the nanoparticles containing naringin showed an effect 5 times greater than the free naringin. Therefore, naringin nanoparticles coated with chitosan were successfully produced with satisfactory physicochemical parameters for the proposed objective, however, an important toxic potential at high doses was observed. As perspectives, it is necessary to evaluate the nanoparticle’s potential for intranasal delivery and neuroprotection, as well as the release profile and activity in more complex animal models for a better development and application of this formulation.